2018
DOI: 10.1016/j.ifset.2017.08.006
|View full text |Cite
|
Sign up to set email alerts
|

DRY biorefineries: Multiscale modeling studies and innovative processing

Abstract: This paper reviews studies on green resource fractionation for two different types of material displaying a lignocellulosic or granular-type structure or a composite of the two. It explains how the identification of specific biochemical or spectral markers helps monitor tissue fate along processing and thus increase our knowledge on material fractionation. The key role of tissue mechanical properties in fracture behavior and the value of characterizing them were highlighted to better understand particle compos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 60 publications
(44 reference statements)
0
13
0
Order By: Relevance
“…In this case, a sorting step (sieving, air classification, or electrostatic separation) can be added to the process diagram. The technologies that can be used and some examples of utilization for lignocellulosic biomass have been reported by Mayer-Laigle et al in 2017 [ 66 ].…”
Section: Discussion: Choice Of Milling Equipmentmentioning
confidence: 99%
“…In this case, a sorting step (sieving, air classification, or electrostatic separation) can be added to the process diagram. The technologies that can be used and some examples of utilization for lignocellulosic biomass have been reported by Mayer-Laigle et al in 2017 [ 66 ].…”
Section: Discussion: Choice Of Milling Equipmentmentioning
confidence: 99%
“…To explore this hypothesis, dry fractionation was carried out to try to obtain fractions with speci c tissue enrichment from leaves, pith, or rind. The particle size obtained in the fractions is not only the result of the e ciency of the grinder but is also due to interactions between plant structures and mechanical loading modes developed in the grinder [43]. The particle size could thus re ect differences in grinding ability in relation to the mechanical properties of the tissues.…”
Section: Exploring Variability Of Maize Shoot Powdermentioning
confidence: 99%
“…It is mainly grown for the grain so the stalk biomass can be used for biofuel production. Dry fractionation was applied to obtain fractions that differ in their physical state and composition [43]. In addition to the chemical composition of the maize stalks and corresponding fractions, the present work focused on the physical-chemical properties of particles: original particle size distribution, speci c surface area, and porosity.…”
Section: Introductionmentioning
confidence: 99%
“…The authors have shown that four populations (≤1 μm, ≈20 μm, ≈100 μm, ≈500 μm) appear during the milling steps. However, shear generated by the high shear mill and the pin-mill is more efficient to grind the material at the cellular scale, as these devices favor the particle population around ≈20 μm [ 47 ].…”
Section: Influence Of Milling On the Properties Of Particles (Sizementioning
confidence: 99%